Supramolecular modulation of the mechanical properties of amino acid-functionalized cellulose nanocrystal films. (June 2022) - Gabrielli, V.; Missale, E.; Cattelan, M.; Pantano, M.F.; Frasconi, M.
Abstract: Cellulose nanocrystal (CNC) is a promising building block for the bottom-up assembly of novel lightweight renewable materials. The ability to engineer the interfacial properties of CNC is of paramount importance to develop assembled materials for various applications; yet it remains a challenge to manipulate the supramolecular interactions within the cellulosic nanomaterials in a controlled manner. In this context, we demonstrate in this article how the assembly and mechanical properties of cellulose thin films can be controlled by manipulating the interfacial interactions of TEMPO-oxidized cellulose nanocrystals (TOCNCs) grafted with two different amino acids, arginine and tryptophan. The amino acid grafting onto the cellulose scaffold was confirmed in aqueous solutions by 1 H NMR spectroscopy and in solid form by FTIR and XPS techniques. The surface functionalization of TOCNCs with simple cationic and aromatic groups provides a strategy for tuning the assembly of the nanostructures based on different supramolecular cross-linking interactions, including hydrogen bonds, π–π stacking, and cation–π interactions. In particular, we show that nanocellulose chains cross-linked by the non-covalent cation–π interactions lead to the formation of a laminated superstructure with high deformation and load standing capabilities. Our work provides a versatile strategy for tuning the surface properties of nanocellulose and represents an important step toward the development of sustainable materials with tailored mechanical properties, which will enable a wider application range of this building block all the way from tissue-engineering scaffolds to flexible devices. Graphical abstract: Image 1 Highlights: TEMPO-oxidized cellulose nanocrystals (TOCNCs) were grafted with arginine and tryptophan. Thin films were assembled from the amino acid-modified TOCNCs. The film morphology was affected by TOCNC surface functionalization. The mechanical properties of the thin films can be modulated by the interfacial supramolecular interactions of cellulose.